1998
DOI: 10.1007/bf02737899
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic receptor-induced changes in paracellular resistance across cultures of human cervical cells are mediated by two distinct cytosolic calcium-related mechanisms

Abstract: In human cervical (CaSki) cells, extracellular adenosine triphosphate (ATP) induces an acute decrease in the resistance of the lateral intercellular space (RLIS), phase I response, followed by an increase in tight junctional resistance (RTJ), phase II response. ATP also stimulates release of calcium from intracellular stores, followed by augmented calcium influx, and both effects have similar sensitivities to ATP (EC50 of 6 microM). The objective of the study was to determine the degree to which the changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…1g-j). Previous studies also reported preferential sorting of the P2X 7 receptor into apical domains of the plasma membrane in cervical epithelial cells [40], as well as of other purinergic receptors (P2Y 2 and P2X 4 [47][48][49][50]). However, the biological significance of these findings is at present unclear.…”
Section: Discussionmentioning
confidence: 92%
“…1g-j). Previous studies also reported preferential sorting of the P2X 7 receptor into apical domains of the plasma membrane in cervical epithelial cells [40], as well as of other purinergic receptors (P2Y 2 and P2X 4 [47][48][49][50]). However, the biological significance of these findings is at present unclear.…”
Section: Discussionmentioning
confidence: 92%
“…1A). ATP phase-I and phase-II responses were previously described and characterized (25)(26)(27). However, until recently, less was known about the phase-III response, and one of our objectives was to better understand the mechanisms that mediate the ATP-induced late decrease in R TE .…”
Section: Atp Effects On Paracellular Permeabilitymentioning
confidence: 98%
“…The P2X 4 effect is mediated by increased Ca 2+ influx, Ca 2+ i -dependent activation of phospholipase (PL)-D, upregulation of diacylglycerol and PKC-mediated threonine dephosphorylation of the tight-junctional protein occludin (Gorodeski, 2002a;Zhu et al, 2006). The data suggest that fluid and solutes secretion in vivo is determined by the combined effects of P2Y 2 and P2X 4 receptors signalling (Gorodeski et al, 1998a). The increases in P2X 7 A immunoreactivity in apical regions of the plasma membranes (facing the lumen) represent P2X 7 A aggregates composing P2X 7 A pores.…”
Section: Endometriummentioning
confidence: 89%
“…HeLa cervical epithelial cells express P2Y 1 , P2Y 2 , P2Y 6 and P2X 7 receptors (Welter-Stahl et al, 2009). Human normal endocervical and ectocervical epithelial cells express P2Y 2 , P2X 4 , and P2X 7 receptors (Meldrum and Burnstock, 1985;Wali and Greenidge, 1989;Pinna et al, 1997;Gorodeski, 1996aGorodeski, , 2008Gorodeski et al, 1994a,b;Gorodeski et al, , 1996Gorodeski and Goldfarb, 1997;Gorodeski et al, 1998a;Gorodeski, 2002b). The P2Y 2 and P2X 4 receptors are located on the apical surface of the epithelial cells (Gorodeski, 2000a,b), and are involved in the regulation of epithelial transport (Gorodeski, 2008).…”
Section: Cervixmentioning
confidence: 96%
See 1 more Smart Citation